Proteomic analysis of Brucella melitensis and Brucella ovis for identification of virulence factor using bioinformatics approachs. (October 2020) - Paci, Valentina; Krasteva, Ivanka; Orsini, Massimiliano; Di Febo, Tiziana; Luciani, Mirella; Perletta, Fabrizia; Di Pasquale, Adriano; Mattioli, Mauro; Tittarelli, Manuela
Abstract: The genus Brucella includes several genetically monomorphic species but with different phenotypic and virulence characteristics. In this study, proteins of two Brucella species, B. melitensis type strain 16 M and B. ovis REO198 were compared by proteomics approach, in order to explain the phenotypic and pathophysiological differences among Brucella species and correlate them with virulence factors. Protein extracts from the two Brucella species were separated by SDS-PAGE and 5 areas, which resulted qualitatively and quantitatively different, were analyzed by nLC-MS/MS. A total of 880 proteins (274 proteins of B. melitensis and 606 proteins of B. ovis ) were identified; their functional and structural features were analyzed by bioinformatics tools. Four unique peptides belonging to 3 proteins for B. ovis and 10 peptides derived from 7 proteins for B. melitensis were chosen for the high amount of predicted B-cell epitopes exposed to the solvent. Among these proteins, outer-membrane immunogenic protein (N8LTS7) and 25 kDa outer-membrane immunogenic protein (Q45321), respectively of B. ovis and B. melitensis, could be interesting candidates for improving diagnostics tests and vaccines. Moreover, 8 and 13 outer and periplasmic non homologue proteins of B. ovis and B. melitensis were identified to screen the phenotypic differences between the two Brucella strains. These proteins will be used to unravel pathogenesis and ameliorate current diagnostic assays. Graphical abstract: Image 1 Highlights: Bioinformatic pipeline to identify potential antigen and non-homologous protein. Eight and 13 non homologues proteins of B. ovis and B. melitensis were identified. Two outer membrane proteins (N8LTS7, Q45321) were selected as candidate antigen.